Foodomics : Advanced Mass Spectrometry in Modern Food Science and Nutrition. - Cifuentes, A. (Wiley-Interscience series on mass spectrometry., 2013)
This book introduces the principles of foodomics through the review of advanced Mass Spectrometry (MS) technologies applied to this new discipline. The coverage details specific ""omics"" approaches based on MS technologies that have been (or can be) applied in foodomics, providing a picture of the most innovative applications and future trends. It explains the fundamental branches of foodomics such as metabolomics, proteomics, and systems biology. And it provides a global perspective on ""omics"" approaches based on MS techniques combined with systems biology in food science and nutrition, a.